Creativity and God In Whitehead's Process Philosophy - Thomas Hidya Tjaya (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2012)
Abstract: The category of creativity unquestionably occupies a central position in Alfred North Whitehead’s philosophy of organism. Its employment is hardly surprising given his project to establish a speculative philosophy that is compatible with modern science. This article examines the use of such a category in this project and argues that the separation between creativity and God causes several problems, including the absence of an ontological principle that may ground the interaction of the various elements in this metaphysical scheme. A more fundamental question is also raised concerning the nature of this project, which walks a fine line between philosophy and science. Keywords: Whitehead, creativity, the Category of the Ultimate, metaphysics, Aristotle, organism, God. Abstrak: Kategori kreativitas jelas memperoleh tempat sentral dalam filsafat organisme Alfred North Whitehead. Kehadiran kategori ini tidaklah mengherankan mengingat usahanya untuk membangun sebuah filsafat spekulatif yang selaras dengan sains modern. Artikel ini hendak mengevaluasi penggunaan kategori ini dan menyampaikan argumen bahwa pemisahan antara kreativitas dan Tuhan memuat sejumlah masalah, termasuk ketiadaan sebuah prinsip ontologis yang dapat menyatukan interaksi berbagai unsur dalam skema metafisika ini. Sebuah pertanyaan lebih mendasar juga diajukan terkait dengan hakikat proyek ini sendiri yang memperlihatkan tipisnya batas antara filsafat dan sains. Kata-kata Kunci: Whitehead, kreativitas, Kategori Pokok, metafisika, Aristoteles, organisme, Tuhan.